Theoretical approaches for the analysis of political dimension in the process of modernization of the higher education - Пашков, В. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The main scientific approaches for the research of political aspects of modernizational processes in the higher education are highlightened in the article. The author identifies and analyzes the sociological, system, institutional, administrative, political-net`s approaches for the analysis of educational changes and policy. It is argued that in the social-humanitarian discourse about the modernization of the higher education through the multidimensionality of educational sphere as a research object these approaches complement each other.